Quality assessment of nata de peña from pineapple (Ananas comosus var comosus) peel - Magallanes, Joane Amanda Love Gallego
This focused on the utilization of pineapple solid waste for the production and quality assessment of nata de piña from unfiltered and filtered mixtures.